STUDI KELAYAKAN EKONOMI PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) DI SUNGAI YEH DIKIS BANJAR LEBAH KABUPATEN TABANAN - Dwi Damarian, Kadek; Dwi Giriantari, Ida Ayu; Jati, I Ketut (Jurnal SPEKTRUM; Vol 10 No 2 (2023): Jurnal SPEKTRUM, 2023)
Micro-hydro Power Plant (MHPP) is a small-scale power plant that uses hydroelectric power as its driving force, such as irrigation canals, rivers or natural waterfalls using the height of the waterfall (head) and the amount of water discharge. Yeh Dikis River, Banjar Lebah, Tabanan Regency is a supporting location for the construction of a Micro Hydro Power Plant (MHPP) which is useful in planning tourism development around the river. The results of measurements and calculations of the current are 0.381 m3/s with a head of 8.2 m. Through the analysis and calculation results, a crossflow turbine with a capacity of 18.15 kW is obtained. The generator used is an alternator with a rotational speed of 1500 rpm. The energy potential that can be generated with a turbine efficiency of 0.75 and a generator efficiency of 0.9 is 15,516 kW. The investment cost to build a PLTMH located on the Yeh Dikis River, Banjar Lebah Tabanan Bali is IDR 372,593,629. The NPV discount rate used is 10% and 12%, the value becomes IDR 305,254,944.69 and IDR 241,046,517.53. IRR is 37.8% and 46.0%, BCR is 0.82 and 0.65; BEP per unit is obtained by selling 1,284,609 kWh of energy. The construction of a MHPP on the Yeh Dikis River, Banjar Lebah, Tabanan, Bali is said to be feasible and capable of obtaining a return on capital in at least 5 years.